Kinematics of the pull shot of the Malaysian national cricket batsmen - - Muhammad Zia ul Haq, Low Jeffrey Fook Lee, Dasril Bendri, (Kinematics, 2017)
Kinematics of the pull shot of the Malaysian national cricket batsmen by - Muhammad Zia ul Haq, Low Jeffrey Fook Lee, Dasril Bendri,